Spectrum of Lower Gastrointestinal Disease on Colonoscopy and Histopathological Examination in a Tertiary Care Centre in Biratnagar - Parajuli, Pawan; Poudyal, Roshana; Koirala, Puru (Journal of Nobel Medical College, 2025)
Background: Colonoscopy is a key diagnostic tool for assessing lower gastrointestinal disorders. Understanding its indications, disease patterns, and histopathological findings is crucial for improving patient care. This study aimed to investigate the common indications for colonoscopy, gastrointestinal disease patterns, and histopathological results. The primary objectives were to determine common colonoscopy indications, understand gastrointestinal disease patterns, and analyse histopathological findings. Materials and Methods: This is a prospective, cross-sectional study conducted at Birat Medical College and Teaching Hospital, Biratnagar, over the period of three months. Patients under 15years of age, with incomplete procedures, or lacking histopathology reports despite undergoing tissue sampling, pregnant women were excluded. Standardized bowel preparation with 4L polyethylene glycol was used. Data collected included demographics, clinical indications, colonoscopic findings, and biopsy results. Results: A total of 341 patients (mean age 46.7 ± 15.7 years) were included. Common indicationswere blood-mixed stools (33.4%), altered bowel habits (27%), and abdominal pain (23.2%). Findings showed normal results in 45.2%, polyps in 16.1%, and inflammatory bowel disease (IBD) in 10%. Histopathological analysis revealed polyps (35%), IBD (20.4%), and malignancy (13.4%). Conclusion: Colorectal cancer was most common in patients with per-rectal bleeding, while polyps were prevalent in those with altered bowel habits. Blood-mixed stools, altered bowel habits, and abdominal pain are the leading indications for colonoscopy. Polyps and IBD were most commonfindings, with malignancy notable in per-rectal bleeding cases.